Modifikasi Sirkulasi Air Pendingin Alat Destilasi pada Proses Pembuatan Akuades - Marjuni Marjuni; Ori Minarto; Sri Cahyo Wahyono (Jurnal Fisika FLUX, 2021)
Distilled water in the laboratory is highly important since it is a basic requirement in the lab work and/or research. The large use of distilled water in the Faculty of Mathematics and Natural Sciences University of Lambung Mangkurat (FMIPA ULM) obliged to depend on its own by providing the equipment to produce distilled water. The efficiency of water is low during producing one liter distilled water due to 35 liters is needed. Several studies have conducted focusing on the energy efficiency and the use of alternative energy in the distilled water production. Efficiency is not only limited on the heating energy sources, but also the cooling component. One of the attempts is modifying the cooling water circulation in the distillation equipment. It aimed that the cooling water is not wasted but is returned to the circuit. In this study, a cooling water circulation modification was carried out by adding a radiator set, submersible pump and storage tank. The distilled water produced from this circuit will be compared with distilled water from distillation equipment without modification. The parameters compared which are: temperature, volume, electrical conductivity and pH. Our research results show that the modified distillation equipment series is feasible to apply since the electrical conductivity of the resulting distilled water is lower than before modification process and also the sediment attached to the boiler wall is formed slower than the distillation equipment without modification. With the need for a lower volume of raw water, a series of modified distillation equipment is also suitable for use in the dry season or during water distribution is not smooth.